2006
DOI: 10.1111/j.1523-536x.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Neonatal Mortality for Primary Cesarean and Vaginal Births to Women with “No Indicated Risk,” United States, 1998–2001 Birth Cohorts

Abstract: Background: The percentage of United States' births delivered by cesarean section has increased rapidly in recent years, even for women considered to be at low risk for a cesarean section. The purpose of this paper is to examine infant and neonatal mortality risks associated with primary cesarean section compared with vaginal delivery for singleton full-term (37-41 weeks' gestation) women with no indicated medical risks or complications. Methods: National linked birth and infant death data for the 1998-2001 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
2
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(153 citation statements)
references
References 23 publications
8
126
2
17
Order By: Relevance
“…In contrast, a study conducted at USA revealed that neonatal mortality rates were higher among infants delivered by cesarean section (1.77 per 1,000 live births) than for those delivered vaginally (0.62). 11 In their study they have considered infant mortality unlike ours for which results might be different.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted at USA revealed that neonatal mortality rates were higher among infants delivered by cesarean section (1.77 per 1,000 live births) than for those delivered vaginally (0.62). 11 In their study they have considered infant mortality unlike ours for which results might be different.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,32,40,42,47,50,53,58,59,62,75,77,85,86,89,94,96,97,109,116,117,125,127,135,137 In contrast, however, the incidence of birth asphyxia, trauma, and meconium aspiration is lower, and these advantages of elective cesarean delivery have been reviewed elsewhere in this issue of Clinics.…”
Section: Respiratory Morbidity In Infants Delivered By Cesarean Deliverymentioning
confidence: 99%
“…These high rates of cesarean section are of concern because the indiscriminate use of this procedure may put the health of mothers and newborns at risk. 7,12,19 Consequently, international organizations, like the World Heath Organization (WHO), the Ministry of Health and researchers have proposed strategies for reducing these rates in Brazil, such as requiring a second opinion in the case of a medical indication for a cesarean section. 1 Moreover, the incidence of this type of birth has been monitored by the Ministry of Health.…”
mentioning
confidence: 99%